2021
DOI: 10.3174/ajnr.a7220
|View full text |Cite
|
Sign up to set email alerts
|

Flow Diversion of Posterior Circulation Aneurysms: Systematic Review of Disaggregated Individual Patient Data

Abstract: BACKGROUND: Experience with endoluminal flow diversion for the treatment of posterior circulation aneurysms is limited. PURPOSE: We sought to investigate factors associated with the safety and efficacy of this treatment by collecting disaggregated patient-level data from the literature. DATA SOURCES: PubMed, EMBASE, and Ovid were searched up through 2019 for articles reporting flow diversion of posterior circulation aneurysms. STUDY SELECTION: Eighty-four studies reported disaggregated data for 301 separate po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 34 publications
2
16
1
Order By: Relevance
“…Chalouhi et al (18) analyzed the complications of 334 coiled large/giant aneurysms and found a trend that posterior circulation aneurysms could predict complications and recurrence. In this study, we demonstrated an overall complication rate of 16.1% (10/62), which was similar to the complication rates of overall posterior circulation aneurysms in published studies (7,(17)(18)(19)(20).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Chalouhi et al (18) analyzed the complications of 334 coiled large/giant aneurysms and found a trend that posterior circulation aneurysms could predict complications and recurrence. In this study, we demonstrated an overall complication rate of 16.1% (10/62), which was similar to the complication rates of overall posterior circulation aneurysms in published studies (7,(17)(18)(19)(20).…”
Section: Discussionsupporting
confidence: 89%
“…Hemorrhagic events are relatively uncommon. Liang et al (17) reported a hemorrhagic event rate of 2.0% in the cohort of 103 large/giant posterior circulation aneurysms and Alwakeal et al (19) demonstrated a hemorrhagic complication of 3.4% in their systematic review. In this study, only 1 (1.6%) patient presented sudden headaches 3 days after the embolization and the cerebellar hemorrhage was found in the following CT scan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review of posterior circulation aneurysm patients reported a 22% rate of major complications after flow diversion, with VBJ and BA aneurysms having the worst outcomes ( 28 ). As shown in Table 4 , the pooled complication rate, morbidity, and mortality among 101 patients with large or giant BA aneurysms treated with FDs was 40, 12.7, and 20.7%, respectively; the overall incidence of adverse outcome was 33.4%.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the fusiform/dissecting morphology and relationship with perforating vessels, SAC of VBA aneurysms was still associated with a high rate of complication in published studies ( 6 , 8 , 9 ). In recent years, flow diversion (FD) has provided an optional method in treating cerebral aneurysms, but there are also potential risks in treating posterior circulation aneurysms ( 10 , 11 ). Intradural large VBA aneurysms are rare and the different outcomes regarding the occlusion rate and the benefits/risks of FD vs. SAC have not been well evaluated.…”
Section: Introductionmentioning
confidence: 99%